2004
DOI: 10.1002/hep.20168
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic transmethylation reactions in micropigs with alcoholic liver disease

Abstract: Alcoholic liver disease is associated with abnormal hepatic methionine metabolism, including increased levels of homocysteine and S-adenosylhomocysteine (SAH) and reduced levels of Sadenosylmethionine (SAM) and glutathione (GSH). The concept that abnormal methionine metabolism is involved in the pathogenesis of alcoholic liver disease was strengthened by our previous findings in a micropig model where combining dietary folate deficiency with chronic ethanol feeding produced maximal changes in these metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 49 publications
6
70
0
Order By: Relevance
“…Since, during the creation of stable cell lines, the vector has to integrate into the genome, the extent of AdoHcyase overexpression and thus, activity strongly depends on the number of integrated vector fragments (encoding AdoHcyase). This observation is consistent with previous results showing that AdoHcyase activity positively correlates with AdoHcyase mRNA levels [3,21,28]. Moreover, the isolation of several clones with different AdoHcyase activities is a valuable tool to study if AdoHcy metabolism is altered in an enzyme-activity dependent manner.…”
Section: Discussionsupporting
confidence: 80%
“…Since, during the creation of stable cell lines, the vector has to integrate into the genome, the extent of AdoHcyase overexpression and thus, activity strongly depends on the number of integrated vector fragments (encoding AdoHcyase). This observation is consistent with previous results showing that AdoHcyase activity positively correlates with AdoHcyase mRNA levels [3,21,28]. Moreover, the isolation of several clones with different AdoHcyase activities is a valuable tool to study if AdoHcy metabolism is altered in an enzyme-activity dependent manner.…”
Section: Discussionsupporting
confidence: 80%
“…A clinical study comparing gene expressions in liver biopsies from ALD patients with those in control normal liver biopsies found decreased transcripts of MS , MAT1A and C β S which could account for observed reduced levels of hepatic SAM and GSH [15] . A subsequent study of livers from ethanol-fed micropigs that developed ALD with a folate deficient diet found decreased transcript expressions of MTHFR , MS , MAT1A , and SAHH [16] , which accounted for reduced hepatic levels of SAM and the SAM/ SAH ratio with increased levels of homocysteine and SAH in this animal model [7] . Whereas two studies found excellent correlations of liver SAM and GSH levels in experimental ALD [7,17] , others recently linked ethanol induced oxidative liver injury in a rat model to reduced SAM and GSH levels that were corrected by inhibition of the ethanol oxidizing enzyme cytochrome P4502E1 (CYP2E1), which also induces reactive oxygen species (ROS) [18] .…”
Section: Methionine Cycle and Effects Of Ethanolmentioning
confidence: 80%
“…Studies of hepatocytes from ethanol-fed mice associated elevated SAH levels with increased sensitization of injury pathways to tumor necrosis factor (TNF α ) [54] . The inclusion of dietary folate deficiency with ethanol feeding of micropigs accelerated the onset of the pathology of ALD while increasing plasma homocysteine levels and decreasing liver SAM, the SAM to SAH ratio and GSH levels [7] , as well as reducing the expressions of relevant transmethylation enzymes [16] . Subsequent studies of livers from the same ethanol and control diet fed micropigs demonstrated augmenting effects of the folate deficient diets on the expressions of ethanol-induced enzymes involved in ER stress pathways of lipogenesis and apoptosis [55] .…”
Section: Aberrant Hepatic Methionine Metabolism In the Pathogenesis Omentioning
confidence: 99%
“…SAM depletion and/or a reduced SAM:SAH ratio are important consequences of altered methionine metabolism, as evidenced by the ability of SAM or its metabolic precursor, betaine, to delay disease progression in animal liver disease models and in patients with alcoholic liver disease (Lu et al, 2001;Villanueva and Halsted, 2004). SAM depletion in chronic liver conditions arises from nutritional deficiencies coupled with reduced activity of the methionine metabolism enzyme methionine synthase (MAT1A) and reduced BHMT gene expression (Kharbanda, 2007;Lu et al, 2002).…”
Section: Research Articlementioning
confidence: 99%